2021
DOI: 10.1101/2021.01.23.427880
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

ENHANCED GRAVITROPISM 2encodes a STERILE ALPHA MOTIVE containing protein that controls root growth angle in barley and wheat

Abstract: The root growth angle defines how roots grow towards the gravity vector and is among the most important determinants of root system architecture. It controls water uptake capacity, nutrient use efficiency, stress resilience and as a consequence yield of crop plants. We demonstrated that the egt2 (enhanced gravitropism 2) mutant of barley exhibits steeper root growth of seminal and lateral roots and an auxin independent higher responsiveness to gravity compared to wild type plants. We cloned the EGT2 gene by a … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 78 publications
(84 reference statements)
0
2
0
Order By: Relevance
“…That such a well-studied gene has only recently been shown to be involved in root system architecture perhaps highlights the comparative lack of research resources wheat root traits have previously been afforded. More recently, the barley root angle mutant enhanced gravitropism 2 (egt2) encoding a STERILE ALPHA MOTIF domain-containing protein has been cloned, which results in narrower and lateral root growth angle compared to wild-type, combined with higher response to gravity in an auxin-independent manner (Kirschner et al 2021). Combining mutations in the A and B genome copies of the orthologous gene in tetraploid wheat resulted in narrower seminal root growth angle, indicating EGT2 could be a target for root-based cereal crop improvement (Kirschner et al 2021).…”
Section: Genetic Control Of Rsa In Wheatmentioning
confidence: 99%
“…That such a well-studied gene has only recently been shown to be involved in root system architecture perhaps highlights the comparative lack of research resources wheat root traits have previously been afforded. More recently, the barley root angle mutant enhanced gravitropism 2 (egt2) encoding a STERILE ALPHA MOTIF domain-containing protein has been cloned, which results in narrower and lateral root growth angle compared to wild-type, combined with higher response to gravity in an auxin-independent manner (Kirschner et al 2021). Combining mutations in the A and B genome copies of the orthologous gene in tetraploid wheat resulted in narrower seminal root growth angle, indicating EGT2 could be a target for root-based cereal crop improvement (Kirschner et al 2021).…”
Section: Genetic Control Of Rsa In Wheatmentioning
confidence: 99%
“…Of course, the one-leaf stage is distant from reproductive and maturity stages, and connections drawn between seedling assay and field traits are speculative. However, correlations and colocations between seminal root traits and agronomic traits have been presented before (Ali et al, 2015;Robinson et al, 2018) and have laid the groundwork for subsequent research that has identified causal genes behind the connections (Feng et al, 2022;Kirschner et al, 2021). More research is required to discover how seminal root trait loci might associate with root phenotypes throughout development in the field and how such phenotypes could impact crop performance and environmental adaptation.…”
Section: Crop Sciencementioning
confidence: 99%
“…In wheat and barley, the gene conditioning enhanced gravitropism 2 ( egt2 ) was identified. The egt2 gene conditions root angle growth in response to gravity (Kirschner et al, 2021). Root elongation in soybean was controlled by the root‐specific expansin gene ( GmEXP1 ), which was located on chromosome 17 (Lee et al, 2003; Lo et al, 2015).…”
Section: Genomic Tools For Root Traitsmentioning
confidence: 99%